The biogeography of fertilization mode in the sea - Keyne Monro; Dustin J. Marshall (Global Ecology and Biogeography, 2015)
Aim Knowledge of the biogeography of life histories is central to understanding and predicting the impacts of global change on key functional traits that shape species distributions and transcend taxonomic boundaries. Whether species are internal or external fertilizers is a fundamental aspect of reproductive diversity in the sea, and has profound ecological and evolutionary consequences. However, geographic variation in this trait and the factors that potentially drive it (e.g. transitions in associated life‐history traits, ecological conditions that favour one mode over the other or the evolutionary history of species) remain poorly characterized. Location Oceans world‐wide. Methods We collated life‐history data (modes of fertilization and development), geographic data and biophysical data (sea‐surface temperatures and food availability) for 1532 marine species spanning 17 invertebrate phyla. We used standard and phylogenetic logistic regressions to evaluate latitudinal gradients in fertilization mode, plus their interactions with development (transitions from planktonic to aplanktonic development, or from feeding to non‐feeding larvae) and taxonomy. We also explored the dependence of fertilization mode on biophysical variables to understand how ecology potentially contributes to geographic variation in this trait. Results Fertilization mode often varies predictably with latitude, but the exact nature of this relationship depends on developmental mode and the phylum under consideration. Some commonalities were evident, however, with the likelihood of internal fertilization declining at higher latitudes for A nnelida and E chinodermata with aplanktonic development, but increasing at higher latitudes for C nidaria and Porifera with non‐feeding, planktonic larvae. Synergistic effects of temperature and food availability may potentially shape some of these patterns. Main conclusions There are latitudinal gradients in fertilization mode in the sea. The variation among phyla and developmental modes, however, is a complexity that is unexplained by existing theory. Combined effects of recent adaptation and deeper phylogenetic history have probably shaped this systematic variation in the reproductive ecology of marine organisms.